Elementos de influência no apego ao lugar de destino pelos turistas em Minas Gerais - Brito, Lelis Maia de (2019)
The place attachment is understood as an affective and positive link between the tourist and the place and can be defined from the identity and dependence of the place The identity comprises the symbolic, cultural value and the self of the tourist with the place, while dependence are the resources and physical characteristics of the place. These dimensions allow to say that the social and functional elements of a place and the psychological aspects of tourists compose the construction of place attachment. Despite the researches developed in the area, this theme has a research field to be explored. Therefore, the general objective of this research is to understand the elements that influence tourists to create place attachment. This research considered Minas Gerais as a context of study due to its touristic relevance in the national scenario by virtue of gastronomy, architecture, natural landscape and local way of life. The results show that social aspects, such as the feeling of being in the home and the authenticity perceived are the main elements that influence tourists to create place attachment. The theoretical contribution of this research is in the identification and analysis of the social elements of tourists in the process of place attachment. The practical implication of this research allows tourism managers to develop strategic actions with the aim of promoting the attractiveness of the place following the travel behavior and the social elements of tourists.